(untitled) (The Research of Medical Science Review, 2024)
Adolescence is a critical period for growth and development, during which proper nutrition plays a fundamental role in determining long-term health outcomes. This study examines the nutritional disparities between rural and urban adolescents aged 10-15 years in Lower Dir, Khyber Pakhtunkhwa, Pakistan. A cross-sectional design was employed, with 200 participants equally divided between rural (n=100) and urban (n=100) settings. Data on anthropometric measurements and dietary intake were collected and analyzed to assess the nutritional status of the participants. The findings revealed that urban adolescents had a significantly higher Body Mass Index (BMI), with 32.0% classified as overweight or obese, compared to 18.0% in rural adolescents. Urban adolescents also consumed more protein-rich foods, fruits, and vegetables, with 58.0% meeting the recommended dietary intake, compared to 45.0% of their rural counterparts. However, rural adolescents showed a higher prevalence of undernutrition, with 22.0% facing stunting and 15.0% experiencing wasting, while urban adolescents exhibited lower rates of undernutrition. Socioeconomic and environmental factors, including income levels, food accessibility, and educational background, were found to significantly influence these nutritional disparities. The study highlights the pressing need for targeted interventions that address the unique nutritional challenges faced by adolescents in both rural and urban areas to enhance overall adolescent health and development.